Biogeochemical interactions control a temporal succession in the elemental composition of marine communities. (23rd November 2015) - Martiny, Adam C.; Talarmin, Agathe; Mouginot, Céline; Lee, Jeanette A.; Huang, Jeremy S.; Gellene, Alyssa G.; Caron, David A.
Abstract: Recent studies have revealed clear regional differences in the particulate organic matter composition and stoichiometry of plankton communities. In contrast, less is known about potential mechanisms and patterns of temporal changes in the elemental composition of marine systems. Here, we monitored weekly changes in environmental conditions, phytoplankton abundances, and particulate organic carbon, nitrogen, and phosphorus concentrations over a 3‐yr period. We found that variation in the particulate organic matter (POM) concentrations and ratios were related to seasonal oscillations of environmental conditions and phytoplankton abundances. Periods with low temperature, high nutrient concentrations and a dominance of large phytoplankton corresponded to low C : N : P and vice‐versa for warmer periods during the summer and fall. In addition to seasonal changes, we observed a multiyear increase in POM C : P and N : P that might be associated with the Pacific Decadal Oscillation. Finally, there was substantial short‐term variability in all factors but similar linkages between environmental variability and elemental composition as observed on seasonal and interannual time‐scales. Using a feed‐forward neural network, we could explain a large part of the variation in POM concentrations and ratios based on changes in environmental conditions and phytoplankton abundances. The apparent links across all time‐scales between changes in physics, chemistry, phytoplankton, and POM concentrations and ratios suggest we have identified key controls of the elemental composition of marine communities in this region.